Studies on Anti-inflammatory, Antinociceptive and Antipyretic Activities of Ethanol Extract of Azadirachta indica Leaves - Mahabub-Uz-Zaman, M; Ahmed, Nazim Uddin; Akter, Rasheda; Ahmed, Kabir; Aziz, M Shafiqul Islam; Ahmed, M Shamsuddin (Bangladesh Journal of Scientific and Industrial Research, 2009)
The present study was carried out to investigate the anti-inflammatory, antinociceptive and antipyretic activities of the crude ethanol extract of Azadirachta indica leaves on experimental animal model at three different dose level- 1g/kg, 500 mg/kg and 100 mg/kg. For evaluation of the anti-inflammatory property carrageenan induced paw edema served as acute model and cotton pellet induced granuloma formation served as chronic model in rats. The acetic acid induced writhing response and hot plate test were used to assess antinociceptive activity in mice. The antipyretic activity was evaluated on yeast-induced pyrexia in rats. Acute toxicity test was also performed in rats after administration of the extract orally at high dose level (4g/kg). Oral administration of the ethanol extract of A. indica leaves significantly (P<0.05) suppressed the paw edema induced by carrageenan as well as granulomatous tissue formation induced by cotton pellet in rats at high dose level (1g/kg) but no significant effect was observed at 500 mg/kg and 250mg/kg dose level. In addition, ethanol extract obtained from A. indica leaves (1g/ kg) also significantly (P<0.05) attenuated the acetic acid induced writhing response in mice but did not show any significant protective effect on heat induced pain in mice. A significant antipyretic effect (P< 0.05) was noticed with ethanol leaf extract of A. indica leaves at 1g/kg and 500 mg/kg dose level. In acute toxicity study, no mortality was observed at 4 g/kg dose level. The present study also demonstrates the potential anti-inflammatory, analgesic and antipyretic effect of the ethanol extract of Azadirachta indica leaves, which supports the claims by the traditional medicine practitioners. Keywords: Anti-inflammatory, Antinociceptive, Antipyretic, Azadirachta indica DOI: 10.3329/bjsir.v44i2.3672 Bangladesh J. Sci. Ind. Res. 44(2), 199-206, 2009